Permasalahan Strategis Dalam Pengelolaan Arsip Elektronik di Era Digital - Akhmad Fakhrul Rozi (Jurnal Pendidikan, Hukum, Komunikasi, 2025)
Digital transformation has fundamentally changed records management, moving from traditional paper-based systems to more complex electronic systems. This article discusses four key issues in electronic records management: the evolving concept of records, the uncontrolled digital work environment, digital preservation challenges, and the shifting roles and responsibilities of records managers. A review of recent literature shows that effective electronic records management requires new conceptual understandings, sustainable preservation strategies, and adjustments to a dynamic digital work ecosystem. The authors emphasize the importance of institutional reform and human resource capacity building to meet the increasing demands of information governance in the digital age. Without comprehensive strategic action, electronic records risk losing their legal and functional value as tools of accountability and institutional memory.